D-optimal Designs for Quartic Polynomial Model for Mixture Experiment with Three and Four Ingredients - Panda, Mahesh Kumar; Pal, Manisha (Bulletin - Calcutta Statistical Association, 2025)
This article considers a classical optimal design problem of finding saturated D-optimal designs for the quartic polynomial model for mixture experiments. The necessary and sufficient conditions of the optimality criterion are confirmed by using the corresponding equivalence theorem. AMS Subject Classification: 62K05